SS‐31 and NMN: Two paths to improve metabolism and function in aged hearts. Issue 10 (11th August 2020) - Whitson, Jeremy A.; Bitto, Alessandro; Zhang, Huiliang; Sweetwyne, Mariya T.; Coig, Rene; Bhayana, Saakshi; Shankland, Eric G.; Wang, Lu; Bammler, Theo K.; Mills, Kathryn F.; Imai, Shin‐Ichiro; Conley, Kevin E.; et al.
Abstract: The effects of two different mitochondrial‐targeted drugs, SS‐31 and NMN, were tested on Old mouse hearts. After treatment with the drugs, individually or Combined, heart function was examined by echocardiography. SS‐31 partially reversed an age‐related decline in diastolic function while NMN fully reversed an age‐related deficiency in systolic function at a higher workload. Metabolomic analysis revealed that both NMN and the Combined treatment increased nicotinamide and 1‐methylnicotinamide levels, indicating greater NAD + turnover, but only the Combined treatment resulted in significantly greater steady‐state NAD(H) levels. A novel magnetic resonance spectroscopy approach was used to assess how metabolite levels responded to changing cardiac workload. PCr/ATP decreased in response to increased workload in Old Control, but not Young, hearts, indicating an age‐related decline in energetic capacity. Both drugs were able to normalize the PCr/ATP dynamics. SS‐31 and NMN treatment also increased mitochondrial NAD(P)H production under the higher workload, while only NMN increased NAD + in response to increased work. These measures did not shift in hearts given the Combined treatment, which may be owed to the enhanced NAD(H) levels in the resting state after this treatment. Overall, these results indicate that both drugs are effective at restoring different aspects of mitochondrial and heart health and that combining them results in a synergistic effect that rejuvenates Old hearts and best recapitulates the Young state. Abstract : The effects of the mitochondrial‐targeted drugs SS‐31 and NMN were tested on aged mouse hearts. It was found that SS‐31 restores diastolic function, while NMN restores high work systolic function. Both drugs normalized PCr/ATP dynamics and increased mitochondrial NAD(P)H levels in response to a work jump. NMN also raised NAD + levels during the work jump. When given in combination, the drugs increased resting NAD(H) levels, indicating a synergistic effect.